Mycoflora of pistachio rhizosphere affected by Fusarium wilt: Uzbekistan - Nazarova Odina Jumadullaevna; Khujaev Otabek Temirovich (Genius Journals, 2023)
This article presents the results of research conducted in Samarkand and Jizzakh regions. Scientific research was conducted to study the rhizosphere of pistachio sprouts and seedlings, the results of which can be found below
Keywords: Rhizosphere; pistachio sprouts